Functional Dependency as a Marker for Positive SARC-F Screen among Older Persons at the Emergency Department - Edward Chong; Eileen Fabia Goh; Wee Shiong Lim (Annals of Geriatric Medicine and Research)
Background Functional dependency may serve as a marker for positive SARC-F screen (Strength, Assistance with walking, Rise from a chair, Climb stairs and Falls) among older adults at the Emergency Department (ED). We compared functional dependency between SARC-F– (<4) and SARC-F+ (≥4) groups at the ED. Methods A secondary analysis of cohorts from two quasi-experimental studies among patients aged ≥65 years old presenting to the ED of a 1,700-bed tertiary hospital. We compared both groups for baseline characteristics using univariate analyses, and performed multiple linear regression to examine the association between Modified Barthel Index (MBI) and Lawton’s instrumental activities of daily living (IADL) against SARC-F, and binary logistic regression to examine the associations between individual ADL domains and SARC-F+. We compared the area under receiver operating characteristic curves (AUC) to detect SARC-F+ for MBI, IADL, frailty, age, cognition and comorbidity. Results SARC-F+ patients were older (86.4±7.6 years), predominantly female (71.5%) and frail (73.9%), more dependent on walking aids (77.2%), and had lower premorbid MBI (median 90.0 [interquartile range 71.0–98.0]) and IADL (4.0 [2.0–5.0]) (both p<0.001). MBI (β=–0.07, 95% confidence interval [CI] –0.086 to –0.055) and IADL (β=–0.533, 95% CI –0.684 to –0.381) were significantly associated with SARC-F. Dependency in finances (odds ratio [OR]=14.7, 95% CI 3.57–60.2, p<0.001), feeding (OR=12.4, 95% CI 1.45–106, p=0.022), and stair-climbing (OR=10.49, 95% CI 4.96–22.2, p<0.001) were the top three functional items associated with SARC-F. MBI (AUC=0.82, 95% CI 0.77–0.84) and IADL (AUC=0.78, 95% CI 0.72–0.84) showed superior discrimination for SARC-F+ compared to other measures (AUC=0.58–0.70). Conclusion Functional dependency is strongly associated with positive SARC-F screen among older adults at the ED. This highlights the need for increased vigilance, especially in the presence of dependency in relevant domains such as managing finances, feeding, and stair-climbing.